2022
DOI: 10.3390/ijerph19063225
|View full text |Cite
|
Sign up to set email alerts
|

Wolfram Syndrome 1: From Genetics to Therapy

Abstract: Wolfram syndrome 1 (WS1) is a rare neurodegenerative disease transmitted in an autosomal recessive mode. It is characterized by diabetes insipidus (DI), diabetes mellitus (DM), optic atrophy (OA), and sensorineural hearing loss (D) (DIDMOAD). The clinical picture may be complicated by other symptoms, such as urinary tract, endocrinological, psychiatric, and neurological abnormalities. WS1 is caused by mutations in the WFS1 gene located on chromosome 4p16 that encodes a transmembrane protein named wolframin. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 111 publications
(195 reference statements)
0
46
0
Order By: Relevance
“…In recent years, some studies have also shown that WFS1 is linked to type 2 diabetes, autosomal dominant optic atrophy (ADOA), and psychiatric problems 13 15 . WFS1 -associated Wolfram syndrome type 1 (WS1) is defined as a rare autosomal neurodegenerative recessive progressive disease and is also known as DIDMOAD, characterized by diabetes insipidus (DI), childhood onset diabetes mellitus (DM), optic atrophy (OA), and deafness (D) 16 . Wolfram-like syndrome is an uncommon autosomal dominant disease that contains variable clinical manifestations, including sensorineural hearing loss, optic atrophy and/or diabetes mellitus 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have also shown that WFS1 is linked to type 2 diabetes, autosomal dominant optic atrophy (ADOA), and psychiatric problems 13 15 . WFS1 -associated Wolfram syndrome type 1 (WS1) is defined as a rare autosomal neurodegenerative recessive progressive disease and is also known as DIDMOAD, characterized by diabetes insipidus (DI), childhood onset diabetes mellitus (DM), optic atrophy (OA), and deafness (D) 16 . Wolfram-like syndrome is an uncommon autosomal dominant disease that contains variable clinical manifestations, including sensorineural hearing loss, optic atrophy and/or diabetes mellitus 17 .…”
Section: Discussionmentioning
confidence: 99%
“…WFS1 is located in the 4p16.1, containing a total of eight exons, with exon 1 as a noncoding region and exon 8 encoding the large portion of the transmembrane regions and the carboxy terminals of the wolframin protein, which is a type of glycoprotein with nine transmembrane domains [12][13][14]. Pathogenic variants in the WFS1 gene are generally associated with Wolfram syndrome (WS), Wolfram-like syndrome (WLS) and LFSNHL [15].…”
Section: Discussionmentioning
confidence: 99%
“…The current study shows that the WFS1 gene is a key pathogenic gene of Wolfram syndrome, and the dysfunction or deletion of its encoded protein caused by the mutation of this gene is a major factor in the disease occurrence. 90% of WS patients are Wolfram syndrome type 1 (WS1) caused by mutations in the WFS1 gene [12] . WFS1 protein includes 890 amino acids, and according to The Human Gene Mutation Database, a total of 464 mutations of different types of WFS1 gene were reported [13] .In this study,rare double homozygous missense mutations of WFS1 base were found in family C and F probands, which altered protein Arg177Ser for GC528_529delinsTA, occurring at the protein N terminus of the cytoplasm, and another G2105A causes changes in the protein, p.G702D, which occurs at the C terminus of the protein in the ER lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Wolfram syndrome(WS) is a rare autosomal recessive disorder caused by mutations in the WFS1 or CISD2 gene, with a global prevalence of one in 50 0,000 [1] . Patients often present with diabetes mellitus, optic atrophy, diabetes insipidus, sensorineural deafness, abnormal urinary tract, and neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%